The efficacy and safety of core decompression for the treatment of femoral head necrosis: a systematic review and meta-analysis - Hua, Kun-chi; Yang, Xiong-gang; Feng, Jiang-tao; Wang, Feng; Yang, Li; Zhang, Hao; Hu, Yong-cheng (Journal of orthopaedic surgery and research, 2019)
Core decompression (CD) is an important method for the treatment of osteonecrosis of the femoral head (ONFH). Few articles investigate the influence of core decompression on outcomes of ONFH. This study was carried out to observe the safety and effectiveness of core decompression in the treatment of ONFH. A comprehensive literature search of databases including PubMed, Embase, and Cochrane Library was performed to collect the related studies. The medical subject headings used were "femur head necrosis" and "Core decompression." The relevant words in title or abstract included but not limited to "Osteonecrosis of the Femoral Head," "femoral head necrosis," "avascular necrosis of femoral head," and "ischemic necrosis of femoral head." The methodological index for nonrandomized studies was adopted for assessing the studies included in this review. Thirty-two studies included 1865 patients (2441 hips). Twenty-one studies (1301 hips) using Ficat staging standard, 7 studies (338hips) using Association Research Circulation Osseous (ARCO) staging standard, and University of Pennsylvania system for staging avascular necrosis (UPSS) staging criteria for 4 studies (802 hips). All the studies recorded the treatment, 22 studies (1379 hips) were treated with core decompression (CD) alone, and 7 studies (565 hips) were treated with core decompression combined with autologous bone (CD Autologous bone). Nine subjects (497 hips) were treated with core decompression combined with autologous bone marrow (CD Marrow). Twenty-seven studies (2120 hips) documented the number of conversion to total hip replacement (THA), and 26 studies (1752hips) documented the number of radiographic progression (RP). Twenty-one studies recorded the types of complications and the number of cases, a total of 69 cases. The random-effect model was used for meta-analysis, and the results showed that the overall success rate was 65%. The rate of success showed significant difference on the outcomes of different stages. The rate of success, conversion to THA, and radiographic progression showed significant difference on the outcomes of ONFH using different treatments. Core decompression is an effective and safe method of treating ONFH. The combined use of autologous bone or bone marrow can increase the success rate. For advanced femoral head necrosis, the use of CD should be cautious. High-quality randomized controlled trials and prospective studies will be necessary to clarify the effects of different etiology factors, treatments, and postoperative rehabilitation. Until then, the surgeon can choose core decompression to treat ONFH depending on the patient's condition. I Meta-analysis.